Structural and functional heart features in pregnancy with concomitant cardiovascular diseases - A. A. Arakelyants; T. E. Morozova; E. A. Barabanova; E. O. Samokhina (Лечащий Врач)
In a healthy woman with a normal pregnancy, structural and functional changes in the heart are adaptive in nature, are slight and are completely normalized after childbirth. A pregnant woman with heart diseases has reduced adaptive capacity, therefore, at any stage of pregnancy, pathological changes can occur that complicate its course and lead to adverse outcomes. In addition, any pregnancy may develop new heart diseases, which can be fatal. That is why an echocardiographic assessment of structural and functional changes in the heart is necessary both during normal pregnancy and in the background of concomitant cardiovascular diseases.